Genital herpes – diagnosis, treatments, attitudes and response to disclosure amongst members of the UK Herpes Viruses Association. (January 2021) - Nicholson, Marian; O'Farrell, Nigel
A diagnosis of genital herpes may result in psychological as well as physical morbidity. Many patients require on-going help and contact the Herpes Viruses Association (HVA), a UK patient support organisation. The HVA conducts occasional questionnaires relating to various issues surrounding herpes and this study reports on a survey conducted amongst members in 2015. The survey was done using SurveyMonkey and covered diagnosis/treatment, both allopathic and self-help, physical and psychological impact and disclosure to partners. Three hundred and fifty-eight women and 103 men completed the questionnaire. Male respondents were older than women (48.6 versus 42.9 years). The majority were first diagnosed in sexual health clinics. A high proportion had informed partners about the diagnosis and in 83% disclosure did not result in rejection. 57% were taking prophylaxis with more taking treatment episodically rather than continually; 11.3% sourced medications on-line. Alternative treatments were used commonly with Lomaherpan cream ( Melissa officinalis), lidocaine ointment and a diet with reduced arginine and increased lysine the most frequent choices. Other alternative treatments included olive leaf extract, Eleuthercoccus senticosus and vitamin supplements. Women reported being troubled psychologically more than men. Neuropathic pain was reported by 80.4% of the women and 64.1% of the men. Although antiviral treatment is cheap and well-tolerated it is still being refused by some healthcare providers. There still appears to be a considerable degree of stigma experienced by patients which can be mitigated by support from patients' support groups such as the HVA.